DEVELOPMENT OF SOFTWARE FOR EVALUATION OF OF TEXT ORIGINALITY - АСТІСТОВА, Т. І.; СЕДЛЯР, А. О. (Technologies and Engineering, 2025)
Objective. Develop software that combines standard methods and the use of artificial intelligence technologies to evaluate the originality of the text when writing scientific papers. Methods. The development of the software was based on theoretical and experimental studies used to analyze the methods of text recognition generated by artificial intelligence, the selection and analysis of a neural network to identify patterns and corresponding patterns in human and artificial intelligence text writing and the integration of this model into the software. to check the text for originality, the implementation of text analysis technologies. Results. The main results of the work can be divided into three interrelated aspects: analytical, design, and practical, each of which made a significant contribution to the achievement of the goal. The research resulted in a thorough analysis of the subject area, the concept of artificial intelligence, its architecture, the functioning of neural networks and their application to text analysis, the technical characteristics and capabilities of modern AI models, as well as aspects of their integration into the text review process, the issues of academic integrity, including the definition of plagiarism, its types and cultural peculiarities of perception of this phenomenon in the processes of education and research, the theoretical basis for the development of a tool that is able to take into account both technical and ethical aspects. The structure of the program, its algorithms, methods of integration with the API for text analysis and data storage format are considered in detail, and a similarity algorithm is developed, which became the basis for identifying the similarity of texts. This allowed us to create a clear and logical product architecture that ensures its functionality and efficiency. Scientific novelty. An original solution is proposed in the form of an integrated system that combines classical methods of checking text for originality with the recognition of texts created by artificial intelligence, which is an important step towards proving academic integrity in a context where artificial intelligence will be used more and more widely in many areas of our lives. Practical value. Thesoftware for text processing technologies is a comprehensive study aimed at developing a software product capable of effectively detecting plagiarism and analyzing texts created with the help of artificial intelligence. The developed tool opens up new opportunities for combating academic dishonesty, facilitates the automation of routine processes, and supports ethical standards in the field of education and science.